2000
DOI: 10.2527/2000.7871796x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for lactation length and weaning-to-conception interval in genetic evaluations for litter size in swine.

Abstract: Effects of lactation length and weaning-to-conception interval on the subsequent litter size of purebred sows were estimated using an animal model. Data on 2,847 Landrace sows with 7,125 litters born between January 1989 and May 1997 and on 1,234 Yorkshire sows with 2,999 litters born between January 1990 and May 1997 were obtained from two Canadian selection herds. Sows having a lactation of less than 14 d (MMEW) were usually not mated until their second estrus, whereas sows weaned after at least 14 d of lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
(23 reference statements)
2
10
1
1
Order By: Relevance
“…Sterning et al (1990) and Tantasuparuk et al (2001) showed that sows with greater weight loss had longer weaning to estrus interval. Subsequent litter sizes decreased when weaning to estrus interval increased up to 10 days (Marois et al, 2000;Tummaruk et al, 2000). In this study, only 55% of first-parity sows were in estrus within 5 days after weaning, as compared to 73% and 78% of second-and third-parity sows.…”
Section: Discussioncontrasting
confidence: 46%
“…Sterning et al (1990) and Tantasuparuk et al (2001) showed that sows with greater weight loss had longer weaning to estrus interval. Subsequent litter sizes decreased when weaning to estrus interval increased up to 10 days (Marois et al, 2000;Tummaruk et al, 2000). In this study, only 55% of first-parity sows were in estrus within 5 days after weaning, as compared to 73% and 78% of second-and third-parity sows.…”
Section: Discussioncontrasting
confidence: 46%
“…Results obtained for systematic effect of duration of the period from weaning to breeding on the varation of the NBA in this investigation are in agreement with resultats obtained by Betka Logar (2000), Marios et al (2000), Petrovic Milica et al (2003), Urankar Janja et al (2004) and Lukovic (2006).…”
Section: Resultssupporting
confidence: 92%
“…Similar conclusions relevant to the effect of this factor on the variation of the monitored trait were presented by Logar Betka (2000), Marios et al (2000), Urankar Janja (2004) and Lukovic (2006).…”
Section: Resultssupporting
confidence: 78%
“…No obstante, la condición corporal después del destete juega un papel importante en el retorno al estro, y tiene un efecto perjudicial sobre el tamaño de la próxima camada. El IDS en una piara puede reducirse a través de mejores prácticas de manejo, mejoramiento genético, aunque su heredabilidad es baja (Cavalcante-Neto et al, 2008;Marois, Brisbane & Laforest, 2000).…”
Section: Discussionunclassified